Manipulating Cracks with Selective Drying in Binary Solvent Mixture Suspensions - Masato Yamamura (Journal of Chemical Engineering of Japan)
In an evaporating colloidal film adhered to a solid substrate, developing tensile stresses fracture the film above the critical dry film thickness, referred to as the critical cracking thickness (hCCT). Despite its scientific and technological importance, it remains challenging to predict hCCT in suspensions comprising non-ideal solvent mixtures, in which selective drying promotes complex time evolutions in a composition-dependent capillary pressure and thus stress. In this study, we systematically explored hCCT of colloidal suspensions containing methanol, ethanol, and n-propanol–water mixtures as the dispersing medium. The author identified two distinct regimes: (i) a low-alcohol-concentration regime, where hCCT remained constant below a critical alcohol/water mass fraction, and (ii) a high-concentration regime, where hCCT monotonically increased with increasing alcohol content. The critical alcohol content agreed with the pseudo-azeotropic composition, at which the evaporation of the two solvents became non-selective. Measured hCCT converged into a master curve for suspensions with different alcohol species, compositions, and temperatures by introducing alcohol mass fractions normalized by the pseudo-azeotrope composition. This unique scaling suggests that selective drying allows the retention of a low-surface-tension solvent in the suspension, and thereby creating crack-free particulate films.